Efficacy and tolerability of folate-aminopterin therapy in a rat focal model of multiple sclerosis - Elo Petri; Li Xiang-Guo; Liljenbäck Heidi; Gardberg Maria; Moisio Olli; Miner Maxwell; Virta Jenni; Saraste Antti; Srinivasarao Madduri; Pugh Michael; Low Philip S.; Knuuti Juhani; et al. (BMC, 2022)
BackgroundActivated macrophages in the experimental model of multiple sclerosis (MS) express folate receptor-beta (FR-beta), representing a promising target for the treatment of MS. Here, we both evaluated the efficacy of a novel folate-aminopterin construct (EC2319) in a rat focal model of multiple sclerosis (MS) and investigated the utility of Ga-68-labeled 1,4,7-triazacyclononane-1,4,7-triacetic acid-conjugated folate (Ga-68-FOL) for assessing inflammatory lesions. In addition, we investigated whether FR-beta is expressed in the brain of patients with MS.MethodsFocal delayed-type hypersensitivity experimental autoimmune encephalomyelitis (fDTH-EAE) was induced in 40 Lewis rats; 20 healthy Lewis rats were used as controls. Rats were divided into six groups according to the duration of disease (control, acute, or chronic) and intervention (vehicle versus EC2319). Ga-68-FOL analyses, histology, and immunofluorescence of the brain were performed to evaluate the efficacy of subcutaneously administered EC2319 on lesion development. Immunofluorescence was used to assess FR-beta expression in postmortem brain samples from 5 patients with MS and 5 healthy controls.ResultsImmunofluorescence and histological analyses revealed significant reductions in FR-beta expression (P < 0.05) and lesion size (P < 0.01), as well as improved inducible nitric oxide synthase/mannose receptor C type 1 ratios (P < 0.01) in macrophages and microglia during the chronic but not acute phase of fDTH-EAE in EC2319-treated rats. The uptake of IV-injected Ga-68-FOL in the brain was low and did not differ between the groups, but the in vitro binding of Ga-68-FOL was significantly lower in EC2319-treated rats (P < 0.01). FR-beta positivity was observed in chronically active lesions and in normal-appearing white matter in MS brain samples.ConclusionsEC2319 was well tolerated and attenuated inflammation and lesion development in a rat model of a chronic progressive form of MS. Human MS patients have FR-beta -positive cells in chronically active plaques, which suggests that these results may have translational relevance.